Non-bossy social classification - Dinko Dimitrov; Clemens Puppe (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
We consider the problem of how societies should be partitioned into classes if individuals express their views about who should be put with whom in the same class. A non-bossy social aggregator depends only on those cells of the individual partitions the society members classify themselves in. This fact allows us to concentrate on a corresponding 'opinion graph' for each profile of views. By means of natural sovereignty, liberalism, and equal treatment requirements, we characterize the non-bossy aggregators generating partitions in which the social classes are refinements of the weakly connected components of the opinion graph.
urn:nbn:de:swb:90-229971
Keywords: D71; 330; social aggregation; group identity; liberalism; non-bossiness